Consequences of the 1858 Malay-Cham rebellion in Cambodia - Mohamad Zain Musa,; Nik Hassan Shuhaimi Nik Abd. Rahman,; Zuliskandar Ramli,; Adnan Jusoh, (Penerbit UKM, 2013)
The Cambodian Malay-Cham are a single community descended from the Malay Archipelago and the once famous Kingdom of Champa, who have played leading roles in the civil and military administration of their adopted homeland since the fifteenth century. During the nineteenth century however, there was a rebellion led by a Malay-Cham minority against the governor of Cambodia’s eastern province that forced military retaliation by King Ang Duong to crush the rebel force. This article discusses the reasons for, and chronology of, the uprising from a close reading of the contemporary Cham manuscript known as CM39(36). In particular, it considers the role of ‘Po’, a Malay-Cham prince who sided with the Cambodian King in his efforts to defeat the rebels. Po and his followers earned the King’s trust and, as a reward, they were allowed to settle in western Cambodia. CM39(36) offers a detailed description of the rebellion, the Malay-Cham’s subsequent journey to western Cambodia, as well as the relationship between the Malay-Cham and the indigenous Khmers from their first arrival in Cambodia to their resettlement.